Applying regular relief onto conical surfaces of continuously variable transmission to enhance its wear resistance - Dzyura, Volodymyr; Maruschak, Pavlo; Slavov, Stoyan; Dimitrov, Diyan (Transport, 2023)
While investigating the variator transmission of vehicles, the relationship between the technological and service parameters of the working surfaces of conical disks treated by technological methods was established. The service properties are proposed to be enhanced by Regular MicroReliefs (RMRs) created on such surfaces. The optimal technological processing conditions were found, which allow retaining the greatest amount of lubricant. The causes of surface defects, formed on the working surfaces of conical disks of the Continuously Variable Transmission (CVT), are systematized and classified. The wear resistance of such surfaces is proposed to be enhanced by technological methods, in particular, by forming partially RMRs on them. Their application facilitates relaxation processes on the material near to the surface, reduces shear stresses and strains, thus preventing the formation of burrs and extending the life of the conical disks of the CVT. A novel approach for obtaining the toolpaths of the deforming element, based on the so-called “Commis–Voyageur problem” algorithms, is employed in order to research the possibilities for involving that methods in toolpath generation. Dependences between the partial RMR’s formation conditions (deforming forces and feedrate) and microgeometric quality parameters are established. The latter include surface roughness, with a partially RMR applied onto the face surfaces of the test specimen (rotary body). It is found that these microreliefs enhance the ability of oil retaining in plastically deformed traces, formed over the operational surfaces, in comparison with those, that are processed by traditional cutting methods, as turning for example.